Comparison of access to health services among urban-to-urban and rural-to-urban older migrants, and urban and rural older permanent residents in Zhejiang Province, China: a cross-sectional survey - Sha Ma (BMC Geriatrics, 2018)
Abstract Background While much literature reported the access of Chinese older migrants to health services, little was known about the differences among sub-groups of older adults, including urban-to-urban and rural-to-urban migrants, and urban and rural permanent residents. This study aimed to examine the access of these four groups to health services in Zhejiang Province, China and provide an evidence for the development of health services policies. Methods A cross-sectional survey was conducted in community-dwelling older adults (aged 60 years or above) in 2013. Participants were recruited by random sampling. Demographic information and access to health services for the elderly populations were obtained via interviews using a self-designed structured questionnaire. Pearson’s chi-square tests and Cochran-Mantel-Haenszel (CMH) tests were performed to examine the differences in access to health services among the four groups. Binary logistic regression was conducted to explore the associations of participants’ visits to doctors with their group status after controlling confounding factors. Results The two-week hospital visiting rates were significantly lower in migrants (55.56% in rural-to-urban and 62.50% in urban-to-urban) than that in urban and rural permanent residents (67.40 and 82.25%, respectively; p < 0.01). The majority of older adults who received a diagnosis indicating need for hospital treatment accepted the treatment, with no significant difference among the four groups after controlling for health service need (χ 2  = 7.08, p = 0.07). On the other hand, 30.05% of the older adults did not visit a doctor when they got ailments in the past 2 weeks prior to the survey, and 16.42% (33/201) did not receive hospital treatment after receiving a diagnosis indicating need for hospital treatment. Factors including age, marital status, educational attainment, major financial source, and living with family members did not influence health services use. Conclusions Targeted social and health policies integrating the strengths of government, society and families should be implemented to further improve health services use for different groups of older adults.